Bryconamericus pyahu sp. n. (Characiformes, Characidae), a new species from the río Iguazú basin, in Argentina - Azpelicueta, María de las Mercedes (2003)
A new species of the genus Bryconamericus is described from río Iguazú basin in Misiones, Argentina. Bryconamericus pyahu sp. n. is distinguished from all other species by the following combination of characters: low body depth (28.0-34.5 in % of SL); premaxillary teeth of the inner series with 3 to 5 cusps; aligned 3 premaxillary teeth of the outer row tricuspidate, and 3-5 maxillary teeth with 1 to 3 cusps. Also, the new species has 18-20 branched anal-fin rays, large black subcircular humeral spot, wide black lateral band, and 37-39 perforated scales on the lateral line. The new species was collected in the arroyo Tateto, headwaters of the río San Antonio, Iguazú basin.